The Use of Allogeneic Leukocytes Infusion in Cancer Immunotherapy - Tang, Yishu; Zhou, Chunxia; Ma, Wenbo; Wang, Dongmei; Zhang, Shuren (Archives of Clinical and Biomedical Research, 2018)
Mixed allogeneic lymphocyte response has activated considering T lymphocytes and elicit type 1 cytokines which induced antitumor immunity. Using TC-1 cancer model, we demonstrated the response of inactivated allogeneic leukocytes infusion (ALI) to generate antitumor immune response. In TC-1 tumor model, ALI induced a delayed cancer development and a prolonged survival. Our study illustrated that ALI might elicit strong antitumor immune response. The method strategy would be easy and efficient strategy in tumor immunotherapy.